Expression of a novel D4 dopamine receptor in the lamprey brain. Evolutionary considerations about dopamine receptors. - Juan ePérez-Fernández; Manuel eMegías; Manuel A Pombal (Frontiers Media S.A., 2016)
Numerous data reported in lampreys, which belong to the phylogenetically oldest branch of vertebrates, show that the dopaminergic system was already well developed at the dawn of vertebrate evolution. The expression of dopamine in the lamprey brain is well conserved when compared to other vertebrates, and this is also true for the D2 receptor. Additionally, the key role of dopamine in the striatum, modulating the excitability in the direct and indirect pathways through the D1 and D2 receptors, has also been recently reported in these animals. The moment of divergence regarding the two whole genome duplications occurred in vertebrates suggests that additional receptors, apart from the D1 and D2 previously reported, could be present in lampreys. We used in situ hybridization to characterize the expression of a novel dopamine receptor, which we have identified as a D4 receptor according to the phylogenetic analysis. The D4 receptor shows in the sea lamprey a more restricted expression pattern than the D2 subtype, as reported in mammals. Its main expression areas are the striatum, lateral and ventral pallial sectors, several hypothalamic regions, habenula, and mesencephalic and rhombencephalic motoneurons. Some expression areas are well conserved through vertebrate evolution, as is the case of the striatum or the habenula, but the controversies regarding the D4 receptor expression in other vertebrates hampers for a complete comparison, especially in rhombencephalic regions. Our results further support that the dopaminergic system in vertebrates is well conserved and suggest that at least some functions of the D4 receptor were already present before the divergence of lampreys.